2022
DOI: 10.1016/j.jsps.2022.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and perception of public about participation in COVID-19 clinical trials: A study from Egypt and Saudi Arabia

Abstract: Background Pharmaceutical firms are striving to find potential treatments to prevent and treat COVID-19. One of the gold standards to evaluate treatment is a clinical trial; however, the difficulty in patient recruitment could act as a determinant. It is evident from the registry data that very few studies have been conducted involving the population of the Middle East and North Africa (MENA) region. Aim To document knowledge, perception, and attitude of the public from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…Table 3 shows the categorization of the knowledge and awareness scores. By making use of Bloom’s cut-off point criteria [ 29 , 30 ], any score below 60% of the total score was categorized as poor, whereas scores in the range of 60–80% of the total score were categorized as moderate, and scores above 80% of the total score were categorized as good [ 22 ]. For questions assessing participants’ knowledge about CKD, it was observed that very few participants (27.3%) had good knowledge, while the remaining either had moderate (36.6%) (or) poor knowledge (36.1%) regarding CKD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows the categorization of the knowledge and awareness scores. By making use of Bloom’s cut-off point criteria [ 29 , 30 ], any score below 60% of the total score was categorized as poor, whereas scores in the range of 60–80% of the total score were categorized as moderate, and scores above 80% of the total score were categorized as good [ 22 ]. For questions assessing participants’ knowledge about CKD, it was observed that very few participants (27.3%) had good knowledge, while the remaining either had moderate (36.6%) (or) poor knowledge (36.1%) regarding CKD.…”
Section: Resultsmentioning
confidence: 99%
“…For assessing the internal consistency of the different items of different sections of the scale, Cronbach’s alpha was used. Alpha coefficients for all the items of the different sections of the scale were found to be above 0.87 (i.e., greater than the 0.70 threshold), demonstrating excellent reliability of the developed scale [ 19 , 20 , 21 , 22 ]. The alpha coefficients of the different sections of the study questionnaire are as follows: Participants’ knowledge about kidney problems and CKD (α = 0.90); Participants’ awareness of risk factors associated with CKD (α = 0.87); Participants’ awareness of complications associated with CKD (α = 0.88).…”
Section: Methodsmentioning
confidence: 99%
“…These studies in different countries revealed that the results differed among nations and were impacted by the types of human settlements. As a result, while creating health programs for COVID-19 and any future epidemics or pandemics, health and education agencies in various nations should strengthen their preventative measures by building specialized measures aimed at individuals in different settlements [76][77][78][79][80][81][82][83]. Knowledge disparity has been extensively studied in health communication.…”
Section: Discussionmentioning
confidence: 99%
“…This reluctance to participate in biobank research compares with previous surveys conducted in the Arab Middle East demonstrating a low percentage (< 30%) of the public who would agree to participate in clinical trials [ 25 27 ]. A recent study regarding the public's attitudes in Egypt, Jordan, and Saudi Arabia toward participating in Covid-19 clinical trials showed that only 15–17.5% of the surveyed people were willing to participate in such research [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of these dimensions need to be pursued with equal priority. An example of such an approach includes the application of sustainability at Biobank Graz, where its sustainability plan included project management and business planning and involved governance and ethical, legal, and social issues [ 28 ].…”
Section: Discussionmentioning
confidence: 99%